Goal-Oriented Translation Strategies for Nanjing Works in the Republic of China: Insights for Cross-Cultural Communication and Sports Narratives - Yuqing Cheng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
As the political, economic, and cultural hub of the Republic of China, Nanjing produced a wealth of literary works that serve as unique cultural symbols of their era. In today's context, where China actively promotes the "going global" cultural strategy, translating and publicizing these works can significantly enhance cultural exchanges and contribute to global understanding of Chinese narratives. This initiative aligns with the broader goal of effectively telling Chinese stories, including those relevant to sports and teamwork in cross-cultural settings. This study adopts a functional goal-oriented perspective to analyze four key elements of literary translation: text interpretation, text function, cultural distance, and text effect. Examining the current translation status of Nanjing works from the Republic of China, the research identifies cultural gaps and deficiencies in the translation of historical and cultural texts. To address these challenges, three translation strategies are proposed: "literal translation academic," emphasizing precision and scholarship; "function localization," adapting texts for specific audiences and purposes; and "feature folk custom," preserving cultural nuances and local color. The study outlines actionable pathways for the international dissemination of translated works, emphasizing their potential for promoting cross-cultural dialogue and fostering a deeper understanding of Chinese culture. These insights have implications for sports psychology by exploring how translation strategies can enhance global communication, teamwork, and cultural empathy within international sports communities.